2022
DOI: 10.1038/s41598-022-21363-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of curcumin loading on the physicochemical, mechanical and antimicrobial properties of a methacrylate-based experimental dental resin

Abstract: Oral biofilms are directly linked to one of the most common chronic human diseases, dental caries. Resin-based dental materials have significant potential to replace amalgam, however they lack sufficient antimicrobial power. This innovative study investigates a curcumin-loaded dental resin which can be utilized in an antimicrobial photodynamic therapy (aPDT) approach. The study evaluated the effects of curcumin loading on resin physicochemical, mechanical, and adhesive properties, as well as the antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Curcumin has been previously investigated as a PS to mitigate cariogenic microorganisms through PDT [ 16 , 17 , 18 , 19 , 27 , 36 ], mainly in direct contact with the cells in planktonic cultures. However, the parameters utilized in aPDT investigations with curcumin as the photosensitizer are not only inconsistent, but there has been very little investigation of the photochemical reaction and ROS production necessary to generate the desired antimicrobial effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin has been previously investigated as a PS to mitigate cariogenic microorganisms through PDT [ 16 , 17 , 18 , 19 , 27 , 36 ], mainly in direct contact with the cells in planktonic cultures. However, the parameters utilized in aPDT investigations with curcumin as the photosensitizer are not only inconsistent, but there has been very little investigation of the photochemical reaction and ROS production necessary to generate the desired antimicrobial effect.…”
Section: Discussionmentioning
confidence: 99%
“…While there are several PSs that have been of interest for aPDT in dentistry, curcumin has garnered significant attention in this field owing in part to its historical use in other medical fields, and its compatible properties for use in aPDT [ 16 ]. Curcumin presents some important advantages, including having a maximum absorption peak in the blue light wavelengths (i.e., 420–450 nm), its low cost, and its effectiveness at targeting several different pathogenic microorganisms, including S. mutans and C. albicans [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Curcumin is a dye obtained from the root of Curcuma longa and while considered soluble in ethanol and DMSO, it is relatively insoluble in water [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following measurement of three samples per group after 24 h of storage at room temperature, the results were averaged. The colour difference, normalΔE$\Delta E$ of each group compared with the control group (0% wt of graphene) was calculated as follows [31]: normalΔE0.28embadbreak=(normalΔL)2+(normalΔa)2+(normalΔb)21/20.28em$$\begin{equation}\Delta E\; = {\left[ {{{( {\Delta {L^*}} )}^2} + {{( {\Delta {a^*}} )}^2} + {{( {\Delta {b^*}})}^2}}\right]^{1/2}}\;\end{equation}$$where normalΔL$\Delta {L^*}$, normalΔa$\Delta {a^*}$, and normalΔb$\Delta {b^*}$ are the differences in lightness and colour between specimens of each group and control group.…”
Section: Methodsmentioning
confidence: 99%
“…Following measurement of three samples per group after 24 h of storage at room temperature, the results were averaged. The colour difference, Δ𝐸 of each group compared with the control group (0% wt of graphene) was calculated as follows [31]:…”
Section: Colour Measurementmentioning
confidence: 99%
“…The outcomes confirmed that 0.10 wt% curcumin had minimal impact on either flexural strength or shear bond strength, but obviously increased water sorption and solubility. It also showed good antimicrobial effects against S. mutans [41].…”
Section: Flexural Strengthmentioning
confidence: 96%